(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objectives of this study were to determine the most common presentation of carcinoma breast in female population of northern areas of Pakistan. Material and methods: This prospective study was conducted in the Department of Surgery, Fauji Foundation Hospital Rawalpindi from 1st March 2009 to 28th February 2010. 120 patients were included by non-probability convenience sampling. Only female patients with histological proof of carcinoma breast were included in the study. Male patients, patients with recurrent disease and those who refused to give consent were excluded from the study. Results: Mean age was 53.22 years. 92% of the patients were between the ages of 41 to 60 years. Duration of symptoms ranged from 2 months to 2 years. 75 % of patients presented with painless lump, 25 % presented with ulceration and underlying lump, 10 % had nipple discharge, 20 % had weight loss, and 8.3 % had jaundice. Conclusion: All the females above the age 41 years with lump breast should be seen by a surgeon and investigated to rule out carcinoma breast.